2019
DOI: 10.1155/2019/9682318
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Polyphenols in Age-Related Macular Degeneration: Protection against Oxidative Stress and Beyond

Abstract: Age-related macular degeneration (AMD) is a multifactorial disease of the retina featured by degeneration and loss of photoreceptors and retinal pigment epithelium (RPE) cells with oxidative stress playing a role in its pathology. Although systematic reviews do not support the protective role of diet rich in antioxidants against AMD, dietary polyphenols (DPs) have been reported to have beneficial effects on vision. Some of them, such as quercetin and cyanidin-3-glucoside, can directly scavenge reactive oxygen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 96 publications
1
53
0
Order By: Relevance
“…In recent years, more and more attention has been paid to the impact of food on the human body. The development of chronic diseases, autoimmune and neurodegenerative diseases, metabolic diseases, and cancer is positively correlated with oxidative stress [ 1 ]. Oxidative stress, that is, the imbalance of antioxidants and prooxidants in favor of prooxidants, is caused by high levels of reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, more and more attention has been paid to the impact of food on the human body. The development of chronic diseases, autoimmune and neurodegenerative diseases, metabolic diseases, and cancer is positively correlated with oxidative stress [ 1 ]. Oxidative stress, that is, the imbalance of antioxidants and prooxidants in favor of prooxidants, is caused by high levels of reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%
“…A2E also induces production of ROS in response to light exposure, which can lead to RPE cell apoptosis (Wang, Kim, et al, 2017). Therefore, enhancing the antioxidant defense system and inhibiting ROS production are crucial for sustaining the structure and function of retina (Pawlowska, Szczepanska, Koskela, Kaarniranta, & Blasiak, 2019;Xu, Sun, Li, & Sun, 2017). Bilberry ACNs can prevent the photooxidative damage from A2E in RPE cells, as well as protection against membrane permeabilization (Jang, Zhou, Nakanishi, & Sparrow, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Green tea is an important dietary product that contains antioxidative molecules with cytoprotective and anti-in ammatory activities that protect cells from oxidative stress-induced apoptosis [15,16,17]. Catechin compounds, such as (-)-epigallocatechin-3-gallate (EGCG), act as radical scavengers and metal-chelating agents and play roles in various cellular processes; for example, they exert neuroprotective functions, regulate blood pressure, and protect against cardiovascular disease [18,19,20]. Previous studies have reported the protective effects of plant extracts and phenolic compounds against oxidative stress and in ammation induced by FDPs [21,22,23,24], and we hypothesized that green tea components could exert potent protective effects against FDP-induced toxicity.…”
Section: Introductionmentioning
confidence: 99%